Antioxidants do not prevent postexercise peroxidation and may delay muscle recovery - Teixeira, V. H.; Valente, H. F.; Casal, S. I.; Marques, A. F.; Moreira, P. A. (Medicine & Science in Sports & Exercise, 2009)
Purpose: This study aimed to determine the effects of 4 wk of antioxidants (AOX) supplementation on exercise-induced lipid peroxidation, muscle damage, and inflammation in kayakers.